2016
DOI: 10.1063/1.4940884
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-a-chip workshop activities for secondary school students

Abstract: The ability to engage and inspire younger generations in novel areas of science is important for bringing new researchers into a burgeoning field, such as lab-on-a-chip. We recently held a lab-on-a-chip workshop for secondary school students, for which we developed a number of hands-on activities that explained various aspects of microfluidic technology, including fabrication (milling and moulding of microfluidic devices, and wax printing of microfluidic paper-based analytical devices, so-called μPADs), flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 96 publications
1
29
0
1
Order By: Relevance
“…All pupil groups delivered a successful design and were able to satisfactorily evaluate the performance of the device during the testing session, indicating that, despite microfluidics being a new concept to the majority of pupils (only two pupils surveyed had heard of microfluidics prior to the project), it is possible to engage them in this kind of problem-based learning approach with microfluidics. From the questionnaire, 84 % of pupils reported that they liked the activities, similar to the reported satisfaction with short workshops of a more traditional science festival outreach nature (Esfahani et al 2016). However, the advantage of the PBL approach was allowing the schoolchildren the opportunity for deeper learning of microfluidics and greater ownership of the projects/activities.…”
Section: Project Follow-up and Pupils Engagementmentioning
confidence: 68%
See 2 more Smart Citations
“…All pupil groups delivered a successful design and were able to satisfactorily evaluate the performance of the device during the testing session, indicating that, despite microfluidics being a new concept to the majority of pupils (only two pupils surveyed had heard of microfluidics prior to the project), it is possible to engage them in this kind of problem-based learning approach with microfluidics. From the questionnaire, 84 % of pupils reported that they liked the activities, similar to the reported satisfaction with short workshops of a more traditional science festival outreach nature (Esfahani et al 2016). However, the advantage of the PBL approach was allowing the schoolchildren the opportunity for deeper learning of microfluidics and greater ownership of the projects/activities.…”
Section: Project Follow-up and Pupils Engagementmentioning
confidence: 68%
“…7. All these considerations show that the pupils are very keen on the relevance of this type of project (Esfahani et al 2016). Towards the 3rd month, a team from one of the school, accompanied by one of their teachers, came to visit our mechanical workshops and participate in the fabrication of the microfluidic chips.…”
Section: Project Follow-up and Pupils Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, reduced price, has paved the way to the exploration of additive manufacturing as an alternative to traditional 2D fabricating methods typically used before. Except for these printing methods, two-photon polymerization [80][81][82], direct-write techniques [83], inkjet [84], micro-milling [85,86], and bio-printing technologies [87,88] have been widely used as well. More useful information could be found in previous published reviews [28,[89][90][91].…”
Section: D Ice Printingmentioning
confidence: 99%
“…A permanent challenge addressed to the plastic industries is to reduce the dimensions of polymeric micro‐parts (with a weight in the order of milligrams) or micro‐structures on polymer substrates with sub‐micron dimensions . Such features have been reached in the research laboratories, using specific polymers, including poly(dimethylsiloxane), molded on a micro‐featured substrate .…”
Section: Introductionmentioning
confidence: 99%